Implementasi TQM Berbasis Metode Qiraati di TPQ Daarul Jannah Desa Kaligawe Wetan Kecamatan Susukanlebak Kabupaten Cirebon - Muhammad Mahdi (Hadlonah: Jurnal Pendidikan dan Pengasuhan Anak, 2021)
This study uses a qualitative method. The research used is field research. Data collection was carried out by interview, observation and documentation. The steps in building data analysis in this study are building content, entering data, analyzing data, and interpreting data. The results of this study indicate that The implementation of TQM with the qiraati method in the TPQ Daarul Jannah includes several characteristics of TQM, namely: Prioritizing customer satisfaction based on the institution’s vision and mission, conducting periodic surveys to set quality, Solving Problem in the TPQ with a scientific approach, Committing to future vision and institution’s innovation, Working with the team to set targets, Improving management and teaching patterns for continuous system improvement, following routine methodological events for heads and teachers as a form of commitment to education and training; Controlled freedom can be seen from the freedom of the process of moving students to the next level by the teacher, the regular presentation of the institution's vision and mission to build unity of purpose, and the involvement and empowerment of employees in planning and implementing all TPQ activities. Abstrak Penelitian ini menggunakan metode kualitatif. Penelitian yang digunakan adalah penelitian lapangan. Pengumpulan data dilakukan dengan wawancara, observasi (pengamatan) dan dokumentasi. Hasil penelitian ini menunjukan bahwa Implementasi TQM dengan metode qiraati di TPQ Daarul Jannah meliputi beberapa karakteristik TQM yaitu : Visi dan misi yang mengutamakan kepuasan konsumen, Obsesi terhadap kualitas dengan pelaksanaan survey berkala, Pemecahan masalah di TPQ dengan pendekatan ilmiah, Komitmen jangka panjang dengan visi masa depan dan inovasi lembaga, Kerja sama Tim untuk pencapaian target, Penyempurnaan pola manajemen dan pengajaran untuk perbaikan sistem secara berkesinambungan, Kewajiban mengikuti acara metodologi rutin bagi kepala dan guru sebagai bentuk komitmen pendidikan dan pelatihan; Kebebasan yang terkendali bisa diketahu dari kebebasan proses kenaikan jilid oleh guru, pemaparan visi misi lembaga secara rutin untuk membangun kesatuan tujuan, dan adanya keterlibatan dan pemberdayaan karyawan dalam perencanaan dan pelaksanaan semua kegiatan TPQ.